Analisis Postur Tubuh Pekerja Saat Menggunakan Kursi dan Komputer Dengan Metode Rapid Office Strain Assessment (ROSA) di Unit Demin Plant PT. XYZ - Hermawan, Putri Alisia; Lukman, M.; Sarungu, Selvia (Syntax Corporation, 2025)
This study aims to analyze the working posture of operators using chairs and computers in the demineralization unit (demin plant) at PT. XYZ by applying the Rapid Office Strain Assessment (ROSA) method. Prolonged computer use with non-ergonomic postures can cause musculoskeletal disorders. The research method used direct observation of two operators with Nordic Body Map (NBM) questionnaires for initial complaint identification, followed by ROSA analysis. The results show that two operators scored 8 on the ROSA scale, which falls into the very high-risk category. This score indicates that the working posture is not ergonomically appropriate and has the potential to cause musculoskeletal disorders. Contributing factors include improper sitting posture not meeting ergonomic standards, absence of adjustable armrests, monitor position too low with viewing angles of 4.38° and 9.43°, monitor viewing distance of 40-45 cm (less than the 50-70 cm standard), and work equipment that does not fully support optimal comfort. Improvement recommendations include using ergonomic chairs with adjustable features, height-adjustable monitor stands, ergonomic workstations, and providing mousepads and portable keyboards. This study contributes to the application of office ergonomics to prevent musculoskeletal disorders in oil and gas industry workers.